2015
DOI: 10.1111/1471-0307.12198
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lowering salt on the physicochemical, microbiological and sensory properties of São João cheese of Pico Island

Abstract: São João cheeses with varying curd dry salting treatments were made with decreasing levels of salt (sodium chloride): 4 (control), 3, 2 and 1% (w/w), along with the salt-free version. The cheeses were ripened at 11°C over a 40-day period, and the effect of lowering salt on the physicochemical, microbiological and sensory properties of the cheese was studied. Reduced salt resulted in a concomitant moisture decrease with protein increase, ash and sodium reduction among experimental cheeses at the same ripening d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
15
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 36 publications
(81 reference statements)
7
15
3
Order By: Relevance
“…The results are also in contrast with the findings of Lindsay et al (1982) who reported that reduced-sodium Cheddar cheese, containing 1.25% or 1.5% sodium/potassium chloride (1:1), revealed lower saltiness and higher bitterness intensities, as well as more off-flavor than the simple low-salt counterparts, seemingly attributable to the added KCl according to this author. Furthermore, the effect observed in the present study is, again, in contrast to an earlier work of Soares et al (2015) on the effect of decreasing salt, where it was found that São João experimental cheeses with 50%, 75%, and 100% salt reduction were substantially different from the full-sodium control. Therefore, a simple 25% NaCl reduction could easily be feasible as previously found by Soares et al (2015) and probably easily marketed in terms of consumer liking.…”
Section: Sensory Analysiscontrasting
confidence: 99%
See 4 more Smart Citations
“…The results are also in contrast with the findings of Lindsay et al (1982) who reported that reduced-sodium Cheddar cheese, containing 1.25% or 1.5% sodium/potassium chloride (1:1), revealed lower saltiness and higher bitterness intensities, as well as more off-flavor than the simple low-salt counterparts, seemingly attributable to the added KCl according to this author. Furthermore, the effect observed in the present study is, again, in contrast to an earlier work of Soares et al (2015) on the effect of decreasing salt, where it was found that São João experimental cheeses with 50%, 75%, and 100% salt reduction were substantially different from the full-sodium control. Therefore, a simple 25% NaCl reduction could easily be feasible as previously found by Soares et al (2015) and probably easily marketed in terms of consumer liking.…”
Section: Sensory Analysiscontrasting
confidence: 99%
“…Moreover, it was found that there was a slight dip in the protein content of the (1:3) NaCl/KCl-salted cheese at 8 and 40 days of ripening, probably because of a higher resistance to a certain degree in the outflow of whey in this particular cheese (Grummer et al 2012). In general, this finding is similar to that obtained in a previous work by Soares et al (2015), who reported a significant protein increase with sodium reduction at each sampling date throughout ripening. The effect observed by these authors was most likely due to an excessive dehydration of protein cheese matrix as a result from very low salt concentrations applied to the experimental cheeses.…”
Section: Physicochemical Characterizationsupporting
confidence: 89%
See 3 more Smart Citations